2018
DOI: 10.1016/j.otsr.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Simplified internal fixation of fifth metacarpal neck fractures

Abstract: This technique can be used to treat fifth metacarpal neck fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Following 3 months line up all cracks recuperated with mean TAM 264º. No disease, 2ry uprooting, Kwire movement nor injury to tangible part of ulnar nerve was prove [21].…”
Section: Discussionmentioning
confidence: 84%
“…Following 3 months line up all cracks recuperated with mean TAM 264º. No disease, 2ry uprooting, Kwire movement nor injury to tangible part of ulnar nerve was prove [21].…”
Section: Discussionmentioning
confidence: 84%
“…However, there is no agreement. Some use a true lateral view (Amsallem et al., 2018; Strub et al., 2010), some a 25° pronated view (Sadiq and Hussain, 2019), others a 30° supinated view (Poumellec and Dreant, 2017) or a 30° pronated view (Kaynak et al., 2019; Kim and Kim, 2015; Surke et al., 2020; Wong et al., 2015). Leung et al.…”
Section: Discussion About Review Resultsmentioning
confidence: 99%
“…Especially palmar angulation has been intensively debated. While many use an angulation threshold of 40° or even 60° (Cepni et al., 2016; Chen et al., 2020; Eldridge and Apau, 2015; Elmowafy et al., 2018; Facca et al., 2010; Fujitani et al., 2012; Kaynak et al., 2019; Kim and Kim, 2015; Ozturk et al., 2008; Pogliacomi et al., 2017; Potenza et al., 2012; Poumellec and Dreant, 2017; Rhee et al., 2012; Sadiq and Hussain, 2019; She and Xu, 2017), still a maximal angulation of 30° has been the guideline in many recent studies (Amsallem et al., 2018; Galal and Safwat, 2017; Kim and Kim, 2015; Surke et al., 2020; Tank et al., 2018; Winter et al., 2007; Wong et al., 2015). Rotational deformity must also be taken in account, although this rarely is a problem with neck fractures of the fifth metacarpal.…”
Section: Introductionmentioning
confidence: 99%
“…Most current studies have suggested that AIMN is a simple and effective method of treating metacarpal fractures and has a relatively low possibility of complications [ 19 21 ]. This procedure has been emerging as the commonly accepted technique for treating FMNFs.…”
Section: Discussionmentioning
confidence: 99%